PENGARUH HUKUM ISLAM DALAM PENGEMBANGAN HUKUM DI INDONESIA - Hadi, Abdul; Hasan, Shofyan (Universitas Islam Negeri Raden Fatah Palembang, 2015)
Abstract: There is an assumption of some Islamic law experts,which states that Islamic law doesn’t have place to fill thenational law substance. In the circles of societies and universitystudents, thought will be focused on the matter of “match”arguing which one has a higher position. This article willdescribe either the past condition or future view aboutinterrelatedness between Islamic law and national lawdevelopment systematically. This will be interesting if it isviewed from substantive aspect of national law development,which aims at giving justice, certainty, benefit, tranquility, andprosperity for humans’ life.ملخص: ظنّ بعدالعلماء المسلمین ال ذین ھ م مرتبق ون انّ حك م الاسلام یجد المك ان فيالاحكام القومیة. وعند المجتمع والطلبة كان تفكیر وضع لھ اھم ة كب رى لمس ائلالمنازلة ویحث اي مك ان اعلى من مك ان آخر. ستعترض ھ ذه المقال ة اح وال الماضىوالمستقبل عن صلة حكم الااسلام منظم ا. في نسأة حك م الق ومى. ام ا السبب فھوجھ ةالاختواء في نسأة الاحكام القومیة, لانھ یعطى العدال ة والاستفاد والاطمعن ان والسلامةللحیاة فى الاجتماع والوطن وھو یصیر جذابھ و خیر المنافعة.Kata kunci: Hukum Islam